Could Profitability, Activity and Use of Equity Finance Increasing DuPont Model of Return on Equity? Jordanian Case - Warrad, Lina Hani; Nassar, Mahmoud (International Review of Management and Marketing, 2017)
Performance evaluation is very fundamental to make a right decision. Profitability analysis is very important factor in the performance evaluation of all companies, but it is not enough just computing ROE to evaluate performance. It is very important to reveal the factors which are having impact on ROE. For this reason DuPont model is considered to be the essential performance indicator in many studies. Theoretically there is a positive relationship between the DuPont Model of ROE with its three components, total asset turnover, net profit margin, and financial leverage, and a negative relationship with the average total equity. The current study applied on the Jordanian Industrial sectors for the period from 2008 to 2015 to approve the previous fact. Eviews software used, Stability diagnostics, Recursive estimates, Cusum test, Vector auto regression (VAR) model, Ordinary lease square (OLS), Wald coefficient test, and Regression analysis applied. The results revealed that there is a significant effect of total asset turnover on DuPont Model of ROE, there is a significant effect of net profit margin on DuPont Model of ROE, and finally there is no significant effect of financing leverage on DuPont Model of ROE. On the other hand, there is a significant effect of total asset turnover and net profit margin and financing leverage jointly on DuPont Model of ROE. Keywords: Total asset turnover, Net profit margin, Financial leverage, DuPont Model of ROE, Amman Stock Exchange (ASE). JEL Classifications: E44, M14